Fuzzy Control in Environmental Engineering - Chmielowski, Wojciech Z.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is intended for engineers, technicians and people who plan to use fuzzy control in more or less developed and advanced control systems for manufacturing processes, or directly for executive equipment. Assuming that the reader possesses elementary knowledge regarding fuzzy sets and fuzzy control, by way of a reminder, the first parts of the book contain a reminder of the theoretical foundations as well as a description of the tools to be found in the Matlab/Simulink environment in the form of a toolbox. The major part of the book presents applications for fuzzy controllers in control systems for various manufacturing and engineering processes. It presents seven processes and problems which have been programmed using fuzzy controllers. The issues discussed concern the field of Environmental Engineering. Examples are the control of a flood wave passing through a hypothetical, and then the real Dobczyce reservoir in the Raba River, which is located in the upper Vistula River basin in Southern Poland, the control and water management in a cascade of reservoirs, a broadly defined combustion process model, modern water heating systems  and many other.
Keywords: Control engineering; Water; Hydrology; Computational intelligence; Pollution; Environmental sciences -- Mathematics; Control and Systems Theory; Water; Computational Intelligence; Pollution; Mathematical Applications in Environmental Science